Paracoccidioides-host interaction: An overview on recent advances in the paracoccidioidomycosis - De Oliveira, Haroldo C. [UNESP]; Assato, Patrícia A. [UNESP]; Marcos, Caroline M. [UNESP]; Scorzoni, Liliana [UNESP]; De Paula E Silva, Ana C.A. [UNESP]; Da Silva, Julhiany de Fátima [UNESP]; Singulani, Junya de Lacorte [UNESP]; Alarcon, Kaila M. [UNESP]; Fusco-Almeida, Ana M. [UNESP]; Mendes-Giannini, Maria J.S. [UNESP] (Frontiers, 2015)
Paracoccidioides brasiliensis and P. lutzii are etiologic agents of paracoccidioidomycosis (PCM), an important endemic mycosis in Latin America. During its evolution, these fungi have developed characteristics and mechanisms that allow their growth in adverse conditions within their host through which they efficiently cause disease. This process is multi-factorial and involves host-pathogen interactions (adaptation, adhesion, and invasion), as well as fungal virulence and host immune response. In this review, we demonstrated the glycoproteins and polysaccharides network, which composes the cell wall of Paracoccidioides spp. These are important for the change of conidia or mycelial (26°C) to parasitic yeast (37°C). The morphological switch, a mechanism for the pathogen to adapt and thrive inside the host, is obligatory for the establishment of the infection and seems to be related to pathogenicity. For these fungi, one of the most important steps during the interaction with the host is the adhesion. Cell surface proteins called adhesins, responsible for the first contact with host cells, contribute to host colonization and invasion by mediating this process. These fungi also present the capacity to form biofilm and through which they may evade the host's immune system. During infection, Paracoccidioides spp. can interact with different host cell types and has the ability to modulate the host's adaptive and/or innate immune response. In addition, it participates and interferes in the coagulation system and phenomena like cytoskeletal rearrangement and apoptosis. In recent years, Paracoccidioides spp. have had their endemic areas expanding in correlation with the expansion of agriculture. In response, several studies were developed to understand the infection using in vitro and in vivo systems, including alternative non-mammal models. Moreover, new advances were made in treating these infections using both well-established and new antifungal agents. These included natural and/or derivate synthetic substances as well as vaccines, peptides, and anti-adhesins sera. Because of all the advances in the PCM study, this review has the objective to summarize all of the recent discoveries on Paracoccidioides-host interaction, with particular emphasis on fungi surface proteins (molecules that play a fundamental role in the adhesion and/or dissemination of the fungi to host-cells), as well as advances in the treatment of PCM with new and well-established antifungal agents and approaches.
Keywords: Fungi-host interaction; Paracoccidioides brasiliensis Paracoccidioides lutzii; Paracoccidioides pathogenicity and virulence; Paracoccidioidomycosis